Adolescent Depression: Impact of Family Relations - Wang, Ziming (Transactions on Social Science, Education and Humanities Research, 2024)
Depression is a major mental disorder that affects numerous people and causes them to experience depressive episodes. The root of depression usually appears in people’s teenage years. Research have shown that family relations, in particular, has the largest impact on the development and manifestation of depressive symptoms in teenagers. After reviewing pertinent literature, the specific components in family relations that are risk factors and protective factors for depressive symptoms in adolescents are identified. The risk factors for depressive symptoms in teenagers are mostly correlated with negative family emotions and actions, which includes parental criticism and expressed emotions, parental depression, lack of family cohesion and adaptability, lack of parental care, negative family emotional climate, and lack of physical affection and verbal intimacy. The protective factors revolve around adolescents’ ability to recognize and manage negative emotions, which includes emotion regulation, positive family climate and social support, emotion coaching, emotion clarity, and cooperative communication. Four recommendations for parents are offered based on these observed risk factors and protective factors to hinder and prevent the development of depression adolescents. These recommendations are social support, positive family atmosphere, physical affection, and verbal affection. It is hoped that studies in the future can focus on investigating the effectiveness of these recommendations and provide a more detailed and reliable list of recommendations for parents to reduce the chances of depression development in their children.